Enhancement of oxygen surface exchange on epitaxial La0.6Sr0.4Co0.2Fe0.8O3−δ thin films using advanced heterostructured oxide interface engineering. (18th August 2016) - Lee, Dongkyu; Lee, Yueh-Lin; Wang, Xiao Renshaw; Morgan, Dane; Shao-Horn, Yang
Abstract: Abstract : Engineering of a novel heterostructured oxide interface was used to enhance the oxygen surface exchange kinetics of La0.6 Sr0.4 Co0.2 Fe0.8 O3− δ (LSCF113 ) thin films. A single-layer decoration of mixed (LaSr)2 CoO4± δ (LSC214 ) and La1− x Sr x CoO3− δ (LSC113 ) and a double-layer decoration of stacked LSC214 and LSC113 grown on the LSCF113 markedly enhanced the surface exchange coefficients of the LSCF113 by up to 1.5 orders of magnitude relative to the undecorated LSCF113 . It is hypothesized that two different types of surface decorations can enable Sr segregation at the interface and surfaces of LSC113 and LSC214, leading to enhancement of the oxygen surface exchange kinetics of decorated LSCF113 .